Resolution of Paraneoplastic Collagenous Enterocolitis after Resection of Colon Cancer - Hugh J Freeman; Ken W Berean (Canadian Journal of Gastroenterology)
A 52-year-old woman developed severe watery diarrhea, weight loss, anemia and hypoalbuminemia. A localized colon cancer was detected. Subsequently, extensive collagenous mucosal involvement of the small and large intestine was discovered. After resection of the colon cancer, her symptoms resolved. In addition, resolution of the inflammatory process occurred, including the subepithelial collagen deposits. Despite extensive small and large intestinal involvement, both clinical and histological resolution of collagenous inflammatory disease was evident. Collagenous enterocolitis is an inflammatory process that may represent a distinctive and reversible paraneoplastic phenomenon.